SENAM LANSIA SEBAGAI UPAYA MENJAGA KEBUGARAN PADA LANSIA DI POSYANDU MELATI ARUM JEBRES SURAKARTA - Widarti, Rini; Irma Mustika Sari; Hermawati (Universitas 'Aisyiyah Surakarta, 2025)
Physical fitness is a crucial aspect for the elderly to maintain independence and quality of life. The decline in bodily functions with age often leads to a decrease in their fitness. Regular and planned interventions are needed to maintain their physical condition. This community service activity aims to improve the physical fitness of the elderly through outreach and the practice of elderly exercises at Posyandu Melati Arum Jebres Surakarta. The method used in the outreach was a participatory rural appraisal approach, involving the active participation of 24 elderly individuals at Posyandu Melati Arum Jebres Surakarta. The results of the community service prior to the activity showed that 83% of the elderly understood the benefits of the exercise, while 17% did not. After the activity was implemented, 92% of the elderly at the Posyandu understood the benefits of the elderly exercise, and 8% did not. This exercise has now become a routine program at the Posyandu